Two decades of research in human movement science in Costa Rica: Future growth and development - Daniel Rojas-Valverde (Pensar en Movimiento)
This manuscript provides a thorough analysis of the two-decade study of human movement science in Costa Rica, emphasizing the noteworthy expansion and advancement of the field. To enhance athletic performance, avoid injuries, treat diseases, and encourage physical exercise, researchers in Costa Rica have developed in-depth analyses, from the basic mechanics of human movement to the development of novel methods and technologies to do so. This article also looks at the potential for Costa Rica to become a leader in the field of human movement science research in the region, as well as its future growth and development. To spur innovation and enhance the outcomes of this research, the author discusses the significance of collaboration with specialists from across the world as well as the requirement for ongoing investment in research and development. The future challenges section provides keys to maintaining the exponential growth of recent years to foster development in issues such as the participation of women in the area, the permanent renewal of study plans, and the incorporation of cross-cutting axes of systematization and research in academic and labour processes. Finally, this study offers a path for the development of human movement science research in Costa Rica, with the potential to significantly move forward in the worldwide endeavour to enhance human movement, performance, and health.